Kajian Efektifitas Sistem Drainase Lapangan Bola Berdasarkan Perhitungan Curah Hujan Rancangan Metode Gumbel - Aulia Rahman Oktaviansyah; Muslimatul Mufida (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes the effectiveness of the football field drainage system at Kanjuruhan Stadium, Kepanjen, Malang Regency, in mitigating rainwater pooling to ensure the smooth conduct of matches. The analysis utilized primary and secondary data, incorporating a hydrological assessment based on the Gumbel Method—which yielded a design rainfall of 258.86 mm—and rainfall intensity calculations using the Van Breun formula. The proposed design specifies drainage channels with rectangular cross-sections (widths of 0.40 m, 0.50 m, and 0.75 m), PVC pipes with a 0.12 m diameter, and culverts with a 0.25 m diameter. The planned drainage system is expected to optimally manage rainwater runoff, thereby enhancing the field's functionality and the quality of football match operations.